DEVELOPMENT OF PROJECT-BASED SCIENCE ON MERDEKA CURRICULUM TEACHING MODULES TO IMPROVE MIDDLE SCHOOL STUDENTS’ 21ST-CENTURY LEARNING SKILLS - Roswi Anggraeni Putri; Binar Ayu Dewanti; Sri Setyaningsih (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2024)
In the current implementation of the Merdeka Curriculum, teachers are still dependent on existing teaching modules and have been unable to develop Merdeka Curriculum teaching modules independently. This study aimed to produce a project-based Independent Curriculum teaching module on the topic of temperature and heat. The design used in this study is the development of using a 4D model. In this study, it was limited to staged development. The sampling technique used is simple random sampling. Data analysis techniques in this study include teaching module validation to determine the feasibility of teaching modules. Analysis of the implementation of learning to determine the implementation of learning using teaching modules. Analysis of 21st-century skills (collaboration skills and creativity) used a left-sided t-test and descriptive analysis to determine the achievement of student learning objectives. Data collection techniques in this study include surveys, observations, and literature studies.. The results of this study 1) The results of the teaching module validation obtained very high criteria and were said to be valid. 2) The results of the implementation of learning include excellent criteria. 3) Students' 21st-century skills can be trained using the project-based Independent Curriculum teaching module.